Effect of Capital Expenditure and Return on Assets on Capital Gains of Consumer Non-Cyclicals Companies Listed on the Indonesia Stock E - Sukma Carrie Saraswati; Achmad - Zaenuddin; Luqman - Khakim (Politeknik Negeri Semarang, 2022)
This study aims to determine the influance of Capital Expenditure and Return on Assets on the Capital Gain of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This study uses a quantitative approach, the population is a non-cyclical consumer sector listed in Indonesia Stock Exchange before 2015, as many as 59 company. The sampling was carry out purposively and 35 companies were obtained as samples. Data analysis techniques include descriptive statistical analysis, classical assumption test, multiple linear analysis, hypothesis testing (t test), and analysis of the coefficient of determination. Data processing was carried out using SPSS version 25. The results of this study indicate that the capital expenditure variable has no effect on capital gains. Meanwhile, the return on assets variable has an effect on capital gains